Brown Spider (Loxosceles genus) Venom Toxins: Tools for Biological Purposes - Andrea Senff-Ribeiro; Silvio Sanches Veiga; Luiza Helena Gremski; Waldemiro Gremski; Rafael Bertoni da Silveira; Oldemir Carlos Mangili; Valéria Pereira Ferrer; Fernando Hitomi Matsubara; Daniele Chaves-Moreira; Ana Carolina M. Wille; Dilza Trevisan-Silva; Olga Meiri Chaim (Toxins, 2011)
Venomous animals use their venoms as tools for defense or predation. These venoms are complex mixtures, mainly enriched of proteic toxins or peptides with several, and different, biological activities. In general, spider venom is rich in biologically active molecules that are useful in experimental protocols for pharmacology, biochemistry, cell biology and immunology, as well as putative tools for biotechnology and industries. Spider venoms have recently garnered much attention from several research groups worldwide. Brown spider (Loxosceles genus) venom is enriched in low molecular mass proteins (5–40 kDa). Although their venom is produced in minute volumes (a few microliters), and contain only tens of micrograms of protein, the use of techniques based on molecular biology and proteomic analysis has afforded rational projects in the area and permitted the discovery and identification of a great number of novel toxins. The brown spider phospholipase-D family is undoubtedly the most investigated and characterized, although other important toxins, such as low molecular mass insecticidal peptides, metalloproteases and hyaluronidases have also been identified and featured in literature. The molecular pathways of the action of these toxins have been reported and brought new insights in the field of biotechnology. Herein, we shall see how recent reports describing discoveries in the area of brown spider venom have expanded biotechnological uses of molecules identified in these venoms, with special emphasis on the construction of a cDNA library for venom glands, transcriptome analysis, proteomic projects, recombinant expression of different proteic toxins, and finally structural descriptions based on crystallography of toxins.